2012
DOI: 10.1038/onc.2012.380
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal binding protein-2 regulates response of epithelial ovarian cancer cells to histone deacetylase inhibitors

Abstract: Ovarian cancer survival rates have stagnated in the last 20 years despite the development of novel chemotherapeutic agents. Modulators of gene expression, such as histone deacetylase (HDAC) inhibitors, are among the new agents being used in clinical trials. Predictors of sensitivity to chemotherapy have remained elusive. In this study, we show that the expression of the transcriptional corepressor C-terminal binding protein-2 (CtBP2) is elevated in human ovarian tumors. Downregulation of CtBP2 expression in ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 28 publications
2
40
0
1
Order By: Relevance
“…Standard immunohistochemistry (IHC) with microwave in 0.1 M citrate buffer (pH 6.0) as the antigen retrieval method was performed on FFPE sections using reagents from Vector Laboratories, Inc (Burlingame, CA, USA) as described before [14]. Antibodies used in this study are listed in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Standard immunohistochemistry (IHC) with microwave in 0.1 M citrate buffer (pH 6.0) as the antigen retrieval method was performed on FFPE sections using reagents from Vector Laboratories, Inc (Burlingame, CA, USA) as described before [14]. Antibodies used in this study are listed in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…15 CtBP1 was first identified through its interaction with the C-terminal region of the adenovirus E1A oncoprotein and ability to modulate E1A transforming activities. 6, 7 CtBP functions as a transcriptional regulator by tethering chromatin remodeling proteins, such as histone deacetylases, methyl transferases, and demethylases, to DNA bound transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results demonstrate that the CtBP2 protein level was regulated by a CHIP-dependent ubiquitin-proteasome pathway. UV irradiation decreases the protein level of CtBPs in cancer cells, and CtBPs are stabilized by MG132 treatment [15]. Our data showed that CHIP depletion resulted in up-regulation of the steady-state level of CtBP2 (Fig.…”
Section: Ctbp2 Is Regulated By Chip In a Ubiquitin-proteasome-dependementioning
confidence: 57%
“…In addition, high expression of both proteins has been reported in colon cancer [14]. Recently, elevated CtBP2 has been shown to play a role in ovarian tumorization by modulating histone deacetylase activity [15]. Collectively, these studies indicate that abundance of CtBP proteins is a crucial factor in tumorization and understanding how CtBP proteins are regulated is important.…”
Section: Introductionmentioning
confidence: 97%